Pengembangan E-Modul Berbasis Discovery Learning pada Materi Animalia dan Ekosistem untuk Peserta Didik Kelas X SMA/MA - Moralita Chatri; Tita Yunia Zalni; Irdawati Zalni; Suci Fajrina (Postgraduate, University of Mataram, 2023)
The initial investigation in the research conducted was an interview with a Biology teacher and gave a questionnaire to 21 students of class X MIPA SMAN 12 Bungo to find out the needs of students in e-module teaching materials. The use of teaching materials used by students is still in the form of printed books, LKS, handouts, videos and image media that do not contain concepts about Biology material that is easily understood by students. Therefore, e-modules are needed that can help students in the learning process. It is known that students have difficulty understanding the concepts in Animalia and Ecosystem material, resulting in low learning outcomes. Therefore, e-modules are needed that can help students in the learning process. The purpose of this research is to produce e-modules based on discovery learning on Animalia and Ecosystem materials for class X SMA / MA students who are valid, practical and affective. This type of research is development research using the Plomp model. The Plomp model consists of three phases, namely the preliminary research phase, the design and prototyping phase and the assessment phase. The subjects in this study were students of class X SMAN 12 Bungo. The research data consisted of validation sheets, practicality assessment sheets by teachers and students, observation sheets and learning outcomes in the cognitive, affective and psychomotor domains, as well as multiple choice questions to assess the cognitive domain of students. The results showed that the discovery learning-based e-module with an average value of 93.13% with very valid criteria. The results of the practicality assessment by teachers with very practical criteria with an average value of 83.33% and the practicality assessment by students with very practical criteria with an average value of 87.72%. The effectiveness test found an influence on the learning outcomes of the cognitive, affective and psychomotor domains of students. So in this study it can be concluded that the discovery learning-based e-module on Animalia and Ecosystem material that has been developed is very valid, very practical and very effective which can be used in the learning process.